2013
DOI: 10.1186/1465-9921-14-45
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of aldehydes in cigarette smoke-induced acute airway inflammation

Abstract: BackgroundCigarette smoking (CS) is the most important risk factor for COPD, which is associated with neutrophilic airway inflammation. We hypothesize, that highly reactive aldehydes are critical for CS-induced neutrophilic airway inflammation.MethodsBALB/c mice were exposed to CS, water filtered CS (WF-CS) or air for 5 days. Levels of total particulate matter (TPM) and aldehydes in CS and WF-CS were measured. Six hours after the last exposure, inflammatory cells and cytokine levels were measured in lung tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Elevated protein abundance in BALF suggested increased vascular permeability, a finding that coincided with previous research showing cigarette smoke induces BALF protein augmentation [48]. Our discovery that the induction of total cell and PMN diapedesis were decreased in SHS-exposed Cldn6 TG mice reinforced prior research that demonstrated increased PMN admission into the airways and bronchial tissue of smokers diagnosed with COPD [49].…”
Section: Discussionsupporting
confidence: 87%
“…Elevated protein abundance in BALF suggested increased vascular permeability, a finding that coincided with previous research showing cigarette smoke induces BALF protein augmentation [48]. Our discovery that the induction of total cell and PMN diapedesis were decreased in SHS-exposed Cldn6 TG mice reinforced prior research that demonstrated increased PMN admission into the airways and bronchial tissue of smokers diagnosed with COPD [49].…”
Section: Discussionsupporting
confidence: 87%
“…Previous MS inhalation studies have demonstrated that exposure to the isolated gas/vapor phase (GVP) is mainly associated with histopathological changes in the nose of rats (Friedrichs et al, 2006), which likely reflects the presence of known irritants in the GVP (van der Toorn et al, 2013). The significant reduction in the majority of analyzed GVP constituents in kretek cigarettes relative to 2R4F cigarettes is therefore likely to explain at …”
Section: Discussionmentioning
confidence: 96%
“…Cigarette smoking, a direct activator of inflammation [38], also indirectly causes inflammation via both inhibition of HDAC activity and decrease of HDAC protein levels within macrophages [21, 22], known characteristics of smokers and COPD patients [16, 39]. HDAC2 has a crucial role not only in glucocorticoid function but also in glucocorticoid-resistant COPD pathogenesis [40].…”
Section: 0 Discussionmentioning
confidence: 99%